2017
DOI: 10.3847/1538-4357/aa5b90
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Plane of Black Hole Activity in the Quiescent Regime

Abstract: A correlation among the radio luminosity (L R ), X-ray luminosity (L X ), and black hole mass (M BH ) in active galactic nuclei (AGNs) and black hole binaries is known to exist and is called the "Fundamental Plane" of black hole activity. predicts that the radio/X-ray correlation index, ξ X , changes from ξ X ≈ 0.6 to ξ X ≈ 1.2 − 1.3 when L X /L Edd decreases below a critical value ∼ 10 −6 . While many works favor such a change, there are also several works claiming the opposite. In this paper, we gather from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 110 publications
3
42
0
Order By: Relevance
“…There is then a remarkable area which is potentially capable to unify very different issues of high energy astrophysics connecting X-ray emission, black hole (BH) physics related to accretion processes, and galaxy mergers see, e.g., [2] and [3,4]. The origin of X-ray emission in BH environments is especially viewed as accretion related, and possibly a bridge between galaxy and a galactic BH activity keeping fingerprints of galaxy mergers [5,6,7,8,9,4,10]. There are various studies of the X-ray emission profile, and more generally jet emission, using more or less the Send offprint requests to: 1 For example from XMM-Newton: https://www.cosmos.esa.…”
Section: Introductionmentioning
confidence: 99%
“…There is then a remarkable area which is potentially capable to unify very different issues of high energy astrophysics connecting X-ray emission, black hole (BH) physics related to accretion processes, and galaxy mergers see, e.g., [2] and [3,4]. The origin of X-ray emission in BH environments is especially viewed as accretion related, and possibly a bridge between galaxy and a galactic BH activity keeping fingerprints of galaxy mergers [5,6,7,8,9,4,10]. There are various studies of the X-ray emission profile, and more generally jet emission, using more or less the Send offprint requests to: 1 For example from XMM-Newton: https://www.cosmos.esa.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they concluded that the fundamental plane should be most suitable for radiatively inefficient BH sources. Another form of the fundamental plane for radiatively efficient BHs is established by Dong et al (2014) and Xie & Yuan (2017).…”
mentioning
confidence: 99%
“…However, different correlation slope p is reported in some specified systems, e.g. the radio-loud AGNs (Wang et al 2006;Panessa et al 2007;Li et al 2008), the narrow-line Seyfert 1 galaxies (Yao et al 2018), and the faint/quiescent AGNs (Yuan et al 2009b;Xie & Yuan 2017, but see Mezcua et al 2018). 3 Even within its typical dynamical range, sources with clear deviations to the standard RX correlation are observed in both BHBs (so called "outliers" for BHBs, e.g., Corbel et al 2004;Coriat et al 2011;Jonker et al 2012;Brocksopp et al 2013) and AGNs (e.g., Bell et al 2011;King et al 2011King et al , 2013.…”
Section: Introductionmentioning
confidence: 95%
“…Physically, the standard RX correlation provides strong evidence for a tight connection between the hot X-ray emitting source (usually a hot accretion flow), and the radio 2 A slight offset in the normalization among the full and failed (defined as the case of no transition into the soft state) outbursts are observed in GX 339-4 (Fürst et al 2015). 3 Quiescent BHBs seem to follow the standard RX correlation Plotkin et al 2017), maybe because they are still not dim enough in these observations (e.g., discussions in Xie & Yuan 2017, and a hint in Dincer et al 2018). source (usually a continuous jet), and it is understood under the coupled accretion-jet model, where a scale-invariant jet model is considered (e.g., Heinz & Sunyaev 2003;Merloni et al 2003;Heinz 2004;Yuan & Cui 2005;Xie & Yuan 2016). The physics behind the hybrid RX correlation, as well as its connection to the standard one, on the other hand, remain unclear.…”
Section: Introductionmentioning
confidence: 99%